Cyclic Change of Fatty Acid Composition in Meibum During the Menstrual Cycle - Suzuki, Tomo (Invest Ophthalmol Vis Sci, 2019)
PURPOSE: To evaluate the fatty acid (FA) composition in the meibum of pre- and postmenopausal women and age-matched men. METHODS: This prospective study involved 24 healthy subjects; six premenopausal women in their 30s with a regular menstrual cycle (young-female [yF] group), six postmenopausal women in their 60s (elderly-female [eF] group), and 12 age-matched men (i.e., young-male [yM] and elderly-male [eM] groups, respectively). The menstrual cycle was divided into six phases (phase I–VI). Meibum was obtained from the meibomian gland orifices via a Daviel spoon, and its FA composition was then analyzed via gas chromatography mass spectrometry (GC-MS). Principal component analysis (PCA) was performed on the GC-MS results. RESULTS: The mean FA composition of all subjects was 40% saturated FAs (SFA) and 60% unsaturated FAs (UFAs). The PCA results of all groups indicated two categories (PC1 [77.5%] and PC2 [12.4%]); one consisting of yF-group samples of mainly phase II and III and the other consisting of the yF-group samples of the rest of the cycle, as well as from eF-group, yM-group, and eM-group samples. Each group had a distinctive nature. The FAs that most contributed to PC1 were C(14:0), C(16:0), and C(18:0) in a positive correlation, and C(18:1n9) in a negative correlation. CONCLUSIONS: FA composition noticeably changes during the menstrual cycle and is somewhat affected by sex and age. The ratio of SFAs (C(16:0), C(18:0)) to mono-UFAs (C(18:1n9)) in the FA composition might have an impact on the lipid quality of meibum, thus suggesting alteration of its melting temperature and viscosity.